I limiti metodologici e teorici della ricerca contemporanea in psicoterapia - Ceschi, Maria Vittoria (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The purpose of the article is to present how research in psychotherapy is flawed by methodological and theoretical errors that have to do with both a misconception of the clinical moment as understood along the lines of medical-pharmacological sciences, and with the very purpose of the psychological treatment, which is a healthcare goal. It will be shown how the clinical moment in psychotherapy, unlike medicine or pharmacology where it is considered the final part of the research process, is an independent experimental moment, and is different from any other type of psychological investigation as it represents the moment of investigation of the subject understood in an organic and complete way, otherwise it can’t be examined. For this reason, the standard medical-pharmacological research setting is unable to demonstrate the effectiveness of the treatment because it is unable to distinguish the aspects of suggestion from the specific results of the treatment. The paper concludes by demonstrating how the Freudian approach is, on the contrary, able to distinguish the theoretical validity of constructions from suggestion because it moves within an alternative paradigm that gives autonomy to clinical research by devising an intra clinical experimental protocol. From this perspective, psychoanalytic practice is knowledge oriented and not healthcare oriented. It is precisely the acceptance of a cognitive purpose which ultimately can determine the possibility of therapeutic efficacy.